Universal dynamics of rogue waves in a quenched spinor bose condensate - Siovitz, Ido; Lannig, Stefan; Deller, Yannick; Strobel, Helmut; Oberthaler, Markus K.; Gasenzer, Thomas (Physical review letters, 2023)
Isolated many-body systems far from equilibrium may exhibit scaling dynamics with universal exponents indicating the proximity of the time evolution to a nonthermal fixed point. We find universal dynamics connected with the occurrence of extreme wave excitations in the mutually coupled magnetic components of a spinor gas which propagate in an effectively random potential. The frequency of these rogue waves is affected by the time-varying spatial correlation length of the potential, giving rise to an additional exponent δc≃1/3 for temporal scaling, which is different from the exponent βV≃1/4 characterizing the scaling of the correlation length ℓV∼tβV in time. As a result of the caustics, i.e., focusing events, real-time instanton defects appear in the Larmor phase of the spin-1 system as vortices in space and time. The temporal correlations governing the instanton occurrence frequency scale as tδI. This suggests that the universality class of a nonthermal fixed point could be characterized by different, mutually related exponents defining the evolution in time and space, respectively. Our results have a strong relevance for understanding pattern coarsening from first principles and potential implications for dynamics ranging from the early Universe to geophysical dynamics and microphysics.